The art of survival gender and history in Europe, 1450 - 2000; essays in honour of Olwen Hufton - Harris, Ruth 1958-; Hufton, Olwen H. 1938-; Past and Present Society; Conference 'Gender, Religion, Poverty and Revolution' (Past & present / Supplement, 2006)
His and hers: gender, consumption and household accounting in eighteenth-century England / Amanda Vickery -- Gender and welfare in modern Europe / Jane E. Lewis -- Rooms to share: convent cells and social relations in early modern Italy / Silvia Evangelisti -- Concubinage and the Church in early modern M(c)ơnster / Simone Laqua -- A confessor and his spiritual child: Fran(c)ʹois de Sales, Jeanne de Chantal, and the foundation of the Order of the Visitation / Ruth Manning -- Letters to Lucie: spirituality, friendship, and politics during the Dreyfus Affair / Ruth Harris -- Witchcraft, nostalgia, and the rural idyll in eighteenth-century Germany / Lyndal Roper -- The 'religious sense' in a post-war secular age / Alex Owen -- Olwen Hufton's 'Poor', Richard Cobb's 'People', and the Notions of the longue dur(c)♭e in French Revolutionary historiography / Colin Jones